Effect of Active Dry Yeast Supplementation on Nutrient Digestibility, Rumen Metabolites and Performances of Surti Goat Kids - Pradhan, Sanjay K. (Indian Journal of Animal Nutrition, 2021)
An experiment was conducted to ascertain the effect of active dry yeast (ADY) on the performances, nutrients digestibility and rumen metabolite profile in Surti goat kids. Sixteen male castrated Surti goat kids of average BW 7.53Â±0.08 (4-month-old) were randomly assigned to one of the two different groups with eight animals each. ADY (Saccharomyces Cerevisiae CNCM I-1077) was supplemented in one experimental group at the rate of 2 % of dry matter intake (DMI) ( 10 g) for a period of 120 days including 6 days period of digestibility trial. At the end of the experiment, rumen liquor was collected from all animals 4 hours post feeding to assess for fermentation metabolites. There was a significant improvement (P < 0.05) in final body weight, dry matter intake, feed to body weight gain ratio and digestibility of nutrients except ether extract in ADY supplemented group as compared to non-supplemented group. ADY supplementation significantly increased (P < 0.05) the ruminal pH, TVFA and TCA precipitated nitrogen with a decreased concentration of ammonia and lactic acid in the ruminal fluid. It was concluded that supplementation of ADY (S. Cerevisiae CNCM I-1077) at 2% of DMI is beneficial in terms of performances, nutrient digestibility and rumen fermentation characteristics in Surti goat kids.